Perancangan Aplikasi Penunjang Keputusan Dalam Memprediksi Gelombang Pasang Surut Air Laut Dengan Melihat Tingkah Laku Hewan Menggunakan Metode Sistem Pakar - Sidqi, Muhammad Ilham (JURIKOM (Jurnal Riset Komputer), 2018)
Long before the advent of technology, people had to rely on their observations and experiences predicting the weather. But sometimes the experience is not entirely appropriate when predicting the weather. Observers are researching and reporting that some animals have a sensitivity to the weather around them, allowing the animal to have a chance to find a safe place to shelter from bad weather. People are sometimes unaware of the climate change around them and ignore them so they can sacrifice their lives, let alone those who live in the surrounding seas and beaches. The people who live there are very dependent on weather predictions because bad weather will be fatal like a tidal wave. Therefore, the authors make the design of decision support applications to determine the tidal wave that can occur in the region around the coast and sea. This decision support design uses knowledge of animal behavior such as birds and crabs that are associated with changes in weather around coastal and marine areas. Other desired features of this system are weather forecasts as well as suggestions for people living and making a living there.